N?-(2-methoxy-benzylidene)-N-[4-(3-methyl-3-phenyl-cyclobutyl)-thiazol-2-yl]-chloro-acetic hydrazide: X-ray structure, spectroscopic characterization and DFT studies - Inkaya, Ersin; Dincer, Muharrem; Ekici, Oner; Cukurovali, Alaaddin (Elsevier, 2012)
In this work, the structure of N'-(2-methoxy-benzylidene)-N-[4-(3-methyl-3-phenyl-cyclobutyl)-thiazol-2-yl]-chloro-acetic hydrazide, (C24H24ClN3O2S), was characterized by X-ray single crystal diffraction technique, IR-NMR spectroscopy and quantum chemical computational methods as both experimental and theoretically. The compound crystallizes in the orthorhombic space group P na2(1) with a = 14.4170 (4) angstrom, b = 11.5441(4) angstrom, c = 27.8420 (8) angstrom and Z = 8. X-ray study shows that crystal has two independent molecules in the asymmetric unit. The molecular geometry was also optimized using density functional theory (DFT/B3LYP) method with the 6-311G(d,p) basis set and compared with the experimental data. To determine conformational flexibility, molecular energy profile of the tittle compound was obtained by semi-empirical (AM1) with respect to selected degree of torsional freedom, which was varied from -180 degrees to + 180 degrees in steps 10. From the optimized geometry of the molecule, vibrational frequencies, gauge-independent atomic orbital (GIAO) H-1 and C-13 NMR chemical shift values, molecular electrostatic potential (MEP) distribution, non-linear optical properties, frontier molecular orbitals (FMOs) of the title compound have been calculated in the ground state theoretically. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: X-ray structure determination; IR and NMR spectroscopy; DFT calculations; Cyclobutane; Non-linear optical properties